Responses of Crepis japonica induced by supplemental blue light and UV-A radiation. Issue 2 (23rd December 2016) - Constantino, L. F. da S.; Nascimento, L. B. dos S.; Casanova, L. M.; Moreira, N. dos S.; Menezes, E. A.; Esteves, R. L.; Costa, S. S.; Tavares, E. S.
Abstract : Morphological and chemical parameters of Crepis japonica (L.) D.C. (Asteraceae) are modified in response to blue light and UV-A radiation. Abstract : Crepis japonica (L.) D.C. (Asteraceae), a weed with antioxidant, antiallergenic, antiviral and antitumor properties displays both medicinal properties and nutritional value. This study aims to assess the effects of a supplementation of blue light and UV-A radiation on the growth, leaf anatomical structure and phenolic profile of the aerial parts of Crepis japonica . Plants were grown under two light treatments: W (control – white light), W + B (white light supplemented with blue light) and W + UV-A (white light supplemented with UV-A radiation). We recorded the length, width, and weight of fresh and dry leaves, the thickness of the epidermis and mesophyll, and stomata density. The phenolic profiles of the aqueous extracts of the aerial parts were analyzed by HPLC-DAD. There was an increase in the leaf size, stomatal density, and phenolic production, and a thickening of the mesophyll and epidermis. UV-A radiation increased the phenolic production more than blue light. Blue light and UV-A radiation both improved the production of caffeic acid by about 6 and 3 times, respectively, in comparison to control. This compound was first reported as a constituent of the extract from the aerial parts together with caftaric acid. UV-A also promoted the production of chlorogenic acid (about 1.5 times in comparison to the control). We observed that the morphological and chemical parameters of C. japonica are modified in response to blue light and UV-A radiation, which can be used as tools in the cultivation of this species in order to improve its medicinal properties and nutritional value.